Dealing with sentient surplus: A moral economy of greyhound rehoming. (December 2022) - Stevens, Emily Grace; Baker, Tom; Lewis, Nicolas
This paper explores greyhound rehoming as a practice through which the sentient surplus of New Zealand's racing industry is dealt with. We bring nature-society geography and moral economy scholarship into productive alignment to ask how and to what effect new forms of value are (re)generated from greyhound bodies and lives that have been cast outside the pale of value as surplus. Accounts offered by both literatures tend not to venture beyond the commodity and are yet to fully engage with the entangled nature of morality and the economy. We seek to address these gaps by mapping the workings of a project that attempts to deal with the moral-economic excess of a capitalist nature(culture). By drawing on interviews with five key rehoming actors and an analysis of industry-affiliated documentary material, we trace the material and discursive practices that are aligned around surplus greyhounds in the interest of making value realisable again. Out of our analysis emerge three configurations through which the bodies and labours of these creatures are brought back into the pale of value: as companions-in-waiting, as undead things, and as transformational figures. While these orientations are contested and the value generated from them unevenly distributed, they see value in this capitalist natureculture be reworked so that accumulation can continue. We argue that sentient surplus is a productive paradox that allows the moral and the political to be brought into a fraught but ultimately productive alignment that obscures the contingencies, asymmetries and grim realities of value creation and distribution in greyhound worlds.